2021
DOI: 10.1002/wmh3.454
|View full text |Cite
|
Sign up to set email alerts
|

Chronic health conditions and voter turnout: Results from the 2012 United States presidential election

Abstract: This study examined associations between diagnoses with five chronic health conditions (diabetes, cancer, heart disease, asthma, and arthritis) and turnout in the 2012 US presidential election. We used cross‐sectional survey data from 16 states from the 2013 and 2014 Behavioral Risk Factor Surveillance System. We estimated a logistic regression model with the main dependent variable as a survey item asking respondents if they voted. We also estimated logistic regression models stratified by race/ethnicity to a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Far from reinforcing the effects of marginalization, health problems appear to boost the turnout of racial minorities in the US. African Americans with cancer proved more likely to vote than whites with cancer (Gollust and Rahn, 2015) and a particularly strong diabetes-voting relationship was found among those who identified as Hispanic and multiracial (McGuire et al, 2021b). Clearly, more studies are needed to understand how race, class, and health interact to affect voter turnout (Gollust and Rahn, 2015; Ojeda and Pacheco, 2019).…”
Section: Health and Votingmentioning
confidence: 99%
See 1 more Smart Citation
“…Far from reinforcing the effects of marginalization, health problems appear to boost the turnout of racial minorities in the US. African Americans with cancer proved more likely to vote than whites with cancer (Gollust and Rahn, 2015) and a particularly strong diabetes-voting relationship was found among those who identified as Hispanic and multiracial (McGuire et al, 2021b). Clearly, more studies are needed to understand how race, class, and health interact to affect voter turnout (Gollust and Rahn, 2015; Ojeda and Pacheco, 2019).…”
Section: Health and Votingmentioning
confidence: 99%
“…The diagnosis matters. A US study revealed that people with heart disease were less likely to vote, whereas those with cancer were more likely, reflecting possible differences in disease identity and the advocacy efforts of disease-focused organizations (Gollust and Rahn, 2015; see also McGuire et al, 2021b). A Finnish study of 17 chronic health conditions similarly found that cancer, like COPD/asthma, was positively associated with voting, but turnout was unaffected by heart disease, arthrosis, multiple sclerosis, or kidney disease (Sund et al, 2017).…”
Section: Health and Votingmentioning
confidence: 99%
“…30,31 A relationship between health status and political participation is well established, but the direction and strength of the relationship varies by race/ethnicity, health condition, income, and education. [32][33][34][35][36][37][38] As the focus of this paper is on racial health inequities, I will focus my discussion on the political consequences of health inequities.…”
Section: Population Health As a Policy Feedback Effectmentioning
confidence: 99%
“…Most studies of actual party choices in elections have been conducted in countries using the first-past-thepost electoral system, with results from the UK showing that people in poor health in general [9] or people with depression [10] are more likely to favour Labour over the Conservatives, and in the United States, results show that the Republicans are similarly favoured by those in good health [11]. However, more recent studies of European multiparty systems indicate that poor health is associated with a higher likelihood of voting for right-wing populist parties [12]. Finally, there are also some results indicating that mental health issues may affect voting choices in referendums as well, as was the case with the Brexit referendum [13].…”
Section: Health and Disability Gaps In Politicsmentioning
confidence: 99%